Stepwise control of host–guest interaction using a coordination polymer gel - Rahul Dev Mukhopadhyay (Nature Portfolio, 2018)
Achieving precise control of host–guest interactions in artificial systems is difficult. Here the authors use the thermodynamics of a system in equilibrium to control stepwise release and capture of cyclodextrin (guest) using a coordination polymer as the host and temperature as the stimulus.